2010
DOI: 10.1001/archinternmed.2009.542
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Deep Sedation Until Death in Belgium: A Nationwide Survey

Abstract: Author Contributions: Dr Drekonja had full access to all of the data in the study and takes responsibility for the integrity of the data and the accuracy of the data analysis. Study concept and design: Johnson.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 9 publications
1
52
0
1
Order By: Relevance
“…The estimated frequency of the use of palliative sedation varies considerably in scientific literature, partly due to differences in definition and research setting. Comparable nationwide studies showed frequencies in Europe of 2.5% up to 16% of all deaths 35. Continuous deep sedation was given up to the moment of death in 8.2% of all deaths in The Netherlands in 2005 6…”
Section: Introductionmentioning
confidence: 99%
“…The estimated frequency of the use of palliative sedation varies considerably in scientific literature, partly due to differences in definition and research setting. Comparable nationwide studies showed frequencies in Europe of 2.5% up to 16% of all deaths 35. Continuous deep sedation was given up to the moment of death in 8.2% of all deaths in The Netherlands in 2005 6…”
Section: Introductionmentioning
confidence: 99%
“…Palliative sedation is found to be involved in about 14.5% of all cases (Chambaere, Bilsen, Cohen, Rietjens, et al, 2010).…”
mentioning
confidence: 99%
“…This may lead to sedation not being discussed, or discussed only very late in the disease trajectory when the patient is suffering severely and obtaining her consent has become problematic or even impossible, thereby deflecting decision making to a third party 8. As mentioned above, available research indicates that, in Belgium in 2007, a request was made by the patient in only 10% of all continuous deep sedation (CDS) v cases, and in another 20% while there was no request, the patient had consented to CDS 6…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the reasons why CS should be initiated, existing guidelines leave some room for interpretation. One example of a difference in national practices is that in The Netherlands in 2001, in accordance with a Dutch guideline,4 the initiation of CS was requested or consented to by the patient in 59% of cases,5 while in Belgium in 2007, a request for or a consent to continuous sedation was obtained in only 30% of cases 6. This indicates that there might be many factors influencing whether, why and when medical practitioners decide on CS.…”
Section: Introductionmentioning
confidence: 99%